Communicative Competences: A Reading From Social Representations And Educational Actors (2022)
In the search for the consolidation of the educational quality policy, the Colombian government is concerned with strengthening competency-based training, its design, implementation, monitoring and evaluation in all cycles of the school system; it is part of the permanent improvement of academic performance. Particularly in technical secondary education, training is provided in labour competences aimed at a real articulation of knowledge and know-how. Recognising the practice and symbolic load contained in the development of communicative competences in students and teachers under study and the institutional processes undertaken for the improvement of academic performance constitutes the research effort. Dissonant perspectives on academic performance converge in a public educational institution in the municipality of Los Patios, Norte de Santander. The study assumes a qualitative perspective in order to interpret the meanings and sense of the information obtained in the field research. The methodology corresponds to the interpretative method, qualitative approach of the Symbolic Interactionism research method, its techniques and procedures. They were conceived as a means to carry out the qualitative analysis of social reality, with which to fragment, conceptualise and integrate the data in order to achieve an inductive theorisation process. The interview and documentary review constituted the data search techniques. In order to enrich and give depth to the knowledge, the results of the different techniques used for data collection, i.e. interview and self-reporting, were compared in this study. Similarly, the results were contrasted with the theories that explain the phenomenon studied, which gave rise to the presentation of the orientations towards communicative competences from their social representations.